The Scenario of a Learning Society Model Toward a Positive Paradigm Shift for Communities - Charungkaittikul, Suwithida (Scholar: Human Sciences, 2015)
The study on the scenario of a learning society model toward a positive paradigm shift for communities is a prospective qualitative research where the EDFR (Ethnographic Delphi Futures Research) technique is used. Research purposes are to 1) analyze and synthesize learning society models and a positive paradigm shift for communities from domestic and foreign literature, academic articles and relevant researches; 2) study opinions of experts on learning society development from relevant public and private agencies, positive paradigm of the communities, and, strategies for the development of learning society toward a positive paradigm shift for communities; 3)develop a learning society model toward a positive paradigm shift for communities; and 4) present the learning society model and the strategies for the development of learning society toward a positive paradigm shift for communities. There are 4 research procedures based on the research objectives as follows: Stage 1: Analyze and synthesize learning society models in Thailand and foreign countries, as well as positive paradigm of the communities from literature, academic articles and relevant researches in Thailand and foreign countries from 2003 to present with respect to: 1) social contexts; 2) development direction and policies; 3) components of learning society; 4) relevant individuals and networks; 5) procedures or nature of activities; 6) non-formal education and leisure education activities; 7) success factors; 8) principle of practicing community; 9) problems and obstacles; 10) components leading to the successful implementation of learning society; 11) paradigm and positive paradigm shift for communities; and 12) strategies for the development of learning society. Stage 2: Study opinions of 42 experts on learning society development from relevant public and private agencies, positive paradigm of the communities, and, strategies for the development of learning society toward a positive paradigm shift for communities using in-depth interview, study visit, Delphi Techniques questionnaires, focus group discussion, and so on. Stage 3: Develop a learning society model toward a positive paradigm shift for communities, as well as strategies for the development of learning society toward a positive paradigm shift for communities. Stage 4: Present the learning society model and the strategies for the development of learning society toward a positive paradigm shift for communities: the components of learning society, the model of a learning society model, and the strategic plans for promotion of a learning society model. Finally, it is hoped that the knowledge obtained through this study can effectively promote lifelong learning in all sectors of Thai society and transform the communities into ones of a learning society, guide the establishment of a learning society development strategies of agencies, communities and cities for the sustainable development of the country, and the findings can benefit individuals interested in conducting further research on the subject.